Ecological Da’wah Strategy in Environmental Conservation within the Mitra Jaya Farmers Group Association - Rismawati Cahyani; Muhammad Nasor; Yunidar Cut Mutia Yanti (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study aims to analyze ecological da'wah strategies in environmental conservation efforts at the Mitra Jaya Farmers Group Association in Tanjung Jaya Village, Bangun Rejo Subdistrict, Central Lampung Regency Method − This study employs a qualitative descriptive approach with field research. Data collection was conducted through observation, semi-structured interviews, and documentation, and was analyzed using the Miles and Huberman framework, which includes data reduction, data presentation, and drawing conclusions. Data validity was ensured through triangulation of techniques and sources. Findings − The results reveal that ecological da’wah strategies are integrated by instilling Islamic values in agricultural activities, such as extension services, discussions, and setting an example in environmental conservation. Da’wah is also implemented through spiritual guidance during regular meetings to strengthen the spiritual awareness of the farmers’ group members. This approach encourages active member participation in environmental conservation through environmentally friendly agricultural practices. Social interaction among members contributes to the formation of a shared awareness and behavioral transformation regarding the urgency of environmental sustainability.